Temperature-controlled acoustic surface waves. (6th October 2016) - Cselyuszka, Norbert; Sečujski, Milan; Engheta, Nader; Crnojević-Bengin, Vesna
Abstract: Conventional approaches to the control of acoustic waves propagating along boundaries between fluids and hard grooved surfaces are limited to the manipulation of surface geometry. Here we demonstrate for the first time, through theoretical analysis, numerical simulation as well as experimentally, that the velocity of acoustic surface waves, and consequently the direction of their propagation as well as the shape of their wave fronts, can be controlled by varying the temperature distribution over the surface. This significantly increases the versatility of applications such as sound trapping, acoustic spectral analysis and acoustic focusing, by providing a simple mechanism for modifying their behavior without any change in the geometry of the system. We further discuss that the dependence between the behavior of acoustic surface waves and the temperature of the fluid can be exploited conversely as well, which opens a way for potential application in the domain of temperature sensing.